MUTU SEKOLAH BERDASARKAN KREATIVITAS DAN BUDAYA KERJA GURU - Sriyanto Sriyanto (Universitas Muhammadiyah Purwokerto, 2015)
This study was aimed to analyze the relationship between the quality of schools based on creativity and the work culture of teachers at the primary school level. At the primary school level the phenomenon of teachers as educators and administrative personnel as well, and must master the entire field of science provide workload is quite high. While it demands professionalism of teachers today has become imperative, where teachers must have four competence as a prerequisite for becoming an educator who has been mandated by law. This research was conducted in Banjar District by taking a sample of teachers in 16 elementary schools, with a sample of 124 peoples. The data were collected using a questionnaire, which is then processed using SPSS. The result showed that the hypothesis statement there is a significant relationship between the creativity of teachers to school quality is accepted. Statements contained hypothesis cultural relations work on the quality of school teachers accepted. While the statement of the hypothesis that together the relationship between creativity and the work culture of teachers to school quality is acceptable. This study analyzed the relationship is generally variable, while the follow-up to improve the quality of schools required further research.